A low-cost printed circuit board-based centrifugal microfluidic platform for dielectrophoresis - Nicklas Rondot; Songyuan Yan; Dario Mager; Lawrence Kulinsky (Microsystems & Nanoengineering)
Abstract In recent decades, electrokinetic handling of microparticles and biological cells found many applications ranging from biomedical diagnostics to microscale assembly. The integration of electrokinetic handling such as dielectrophoresis (DEP) greatly benefits microfluidic point-of-care systems as many modern assays require cell handling. Compared to traditional pump-driven microfluidics, typically used for DEP applications, centrifugal CD microfluidics provides the ability to consolidate various liquid handling tasks in self-contained discs under the control of a single motor. Therefore, it has significant advantages in terms of cost and reliability. However, to integrate DEP on a spinning disc, a major obstacle is transferring power to the electrodes that generate DEP forces. Existing solutions for power transfer lack portability and availability or introduce excessive complexity for DEP settings. We present a concept that leverages the compatibility of DEP and inductive power transfer to bring DEP onto a rotating disc without much circuitry. Our solution leverages the ongoing advances in the printed circuit board market to make low-cost cartridges (<$1) that can employ DEP, which was validated using yeast cells. The resulting DEPDisc platform solves the challenge that existing printed circuit board electrodes are reliant on expensive high-voltage function generators by boosting the voltage using resonant inductive power transfer. This work includes a device costing less than $100 and easily replicable with the information provided in the Supplementary material. Consequently, with DEPDisc we present the first DEP-based low-cost platform for cell handling where both the device and the cartridges are truly inexpensive.